Wybrane aspekty promocji innowacji w Euroregionie Nysa - doświadczenia transgraniczne - Adamczuk, Franciszek (Selected Aspects of Innovation Promotion in Euroregion Nisa-Inter-Border Experiences, 2008)
This paper aims to present innovation promotion in The Euroregion Nisa (ERN), and seeks to answer the question: what role in this process plays special promoting venture named "Innovation Eu-roregion Neisse-Nisa-Nysa" (abbr. "Innovation ERN"). As the research shows, this euroregional contest, approved and supported by the ERN authorities and Polish, German, and Czech civil parish and towns associations, stimulates innovation growth and contributes to the popularization of pro-innovation thinking of region and its development. This paper ends with some general recommendations and the author's precise suggestions how to benefit from the ERN economy innovation growth. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 72-80